Fra søstersolidaritet til kulturkrasj - Müftüoglu, Ingrid Birce (Tidsskrift for kulturforskning, 2018)
In this article, descriptions of the Women's culture festival in Oslo in June 1979 serve as a background for an analysis of different understandings of culture within the Women's movement. In several sources, the festival is described as a commemoration of the glorious 1970s when feminism became mainstream. However, the story is twofold: On one side, the festival made visible the diversity within the Women's movement and restored a sense of community. On the other side, the festival was an arena for experimentation with and redefinition of the idea of one collective Women's movement. The article gives an account of the festival from the idea stage, through implementation during festival week and to the disagreements within the Women's movement concerning the way forwards after the festival. This story shows how different understandings of culture became a major conflict within the Women's movement in Norway at the end of the 1970s. Thus, discussions about whether culture should be a means for politics or the other way around changed the views on how to organise the movement and resulted in a less politically active Women's movement during the 1980s.